Hubungan Kebugaran Kardiovaskular dan BMI Terhadap Konsentrasi - Dhara Puspa; Muhammad Nur Alif; Rizal Ahmad Fauzi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to analyze the relationship between cardiovascular fitness, body mass index, and the concentration level of Physical Education students. The method used was a quantitative approach with a correlational design. The research subjects consisted of 20 students selected using purposive sampling technique. Cardiovascular fitness was measured using the Multistage Fitness Test (bleep test) to estimate VO₂max, body mass index was calculated through anthropometric measurements, while concentration level was measured using the Grid Concentration Test. Data analysis was conducted using normality test, linearity test, and Pearson correlation test with the assistance of IBM SPSS software. The results showed that all data were normally distributed and had linear relationships; however, there was no significant relationship between cardiovascular fitness or body mass index and students’ concentration level. In conclusion, cardiovascular fitness and body mass index are not primary predictors in determining students’ concentration levels in this study.   Keywords: Body Mass Index, Cardiovascular Fitness, Concentration, Students